2016
DOI: 10.1002/chem.201600891
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Reversible Circularly Polarized Luminescence Emission of a Chiral 1,8‐Naphthalimide Fluorophore Induced by Excimer Emission and Orderly Aggregation

Abstract: Four chiral 1,2-diaminocyclohexane (DACH)-based molecules (R,R/S,S-2 and R,R/S,S-4) incorporating 1,8-naphthalimide fluorophores exhibit strong circularly polarized luminescence (CPL) emission signals in common organic solvents. Interestingly, the reversed CPL signals can be observed in the aggregated state, which is due to the orderly aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…We speculate that R / S ‐BINOL‐CN luminogens can form highly regular anisotropic and helical self‐assembly in the N*‐LC film unlike the disordered aggregate in the KBr pellet‐dispersed state. Our previous works also demonstrated that chiral 1,2‐DACH‐based compounds incorporating the 1,8‐naphthalimide chromophore group emitted reversal CPL signals from solution to aggregation due to the regular and orderly alignment of the aggregate from disparate solution to aggregation . Furthermore, N*‐LCs at various concentrations of AIE‐active chiral luminogen dopants were also investigated for CPL and liquid crystal behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that R / S ‐BINOL‐CN luminogens can form highly regular anisotropic and helical self‐assembly in the N*‐LC film unlike the disordered aggregate in the KBr pellet‐dispersed state. Our previous works also demonstrated that chiral 1,2‐DACH‐based compounds incorporating the 1,8‐naphthalimide chromophore group emitted reversal CPL signals from solution to aggregation due to the regular and orderly alignment of the aggregate from disparate solution to aggregation . Furthermore, N*‐LCs at various concentrations of AIE‐active chiral luminogen dopants were also investigated for CPL and liquid crystal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous works also demonstrated that chiral 1,2-DACH-based compounds incorporating the 1,8-naphthalimide chromophore group emitted reversal CPL signals from solution to aggregation due to the regulara nd orderly alignment of the aggregate from disparate solution to aggregation. [23] Furthermore,N *-LCs at variousconcentrations of AIEactive chiral luminogen dopantsw ere also investigated for CPL and liquid crystal behavior.A si se vident from Ta ble 1a nd Figure 5a,w ef ound that the helical pitches of N*-LCsb ecome shorter and the CPL g lum values gradually increasew hile the doping weight of R/S-BINOL-CN increases from 0.5 to 2.0 wt %. The max g lum values are À0.40/ + 0.41 at concentration of 2.0 wt %( Ta ble 1).…”
Section: As Shown Inmentioning
confidence: 99%
“…Cogels mixed with different AIE dyes exhibited strong emission ranging from 450 to 600 nm, accompanied by a significant enhancement in luminescent intensity compared with the AIE properties of various undoped‐gel dyes (Figure b). In addition, upon mixing the enantiomer of 184 and various dyes, all the dye‐doped cogels emitted full‐color CPL from 425 to 595 nm, and exhibited mirror‐image signal with the highest g lum up to 1.3 × 10 −3 , which is a comparable value for purely organic assembled materials (Figure c) …”
Section: Supramoleculesmentioning
confidence: 99%
“…By incorporation of 1,8‐naphthalimide fluorophore into chiral 1,2‐diaminocyclohexane (DACH) in molecule 8 , it was also possible to achieve the CPL switching between monomer and excimer emission of 1,8‐naphthalimide by adjusting the solvent composition to finely control the aggregation state (Figure ) . In THF solution, the DACH‐based chiral 1,8‐naphthalimide 8 showed absorption bands at around 230 and 355 nm, which correspond to the absorption of the 1,8‐naphthalimide chromophore unit.…”
Section: Cpl Switching By Promoting the Excimer Formationmentioning
confidence: 99%
“…[18] Most of the relatedr eports have been well summarized by Maeda in 2013. [14] In addition to the assembly structure, other factors, such as excimer formation, [19][20][21][22][23][24] conformation of monomeric fluorophores, [25][26][27][28][29][30][31] electronic nature of p-conjugated skeleton or peripherals ubstituent, [32][33][34][35] and intramolecular charge-transfer (CT) dynamics, [36] maya lso exhibits significant influences on the CPL properties. Our discussion will focus on the strategies to tune the factors that influence CPL properties, which is expected to complementw ell the recent review about polymers and SOMs displayings timuli-responsive CPL.…”
Section: Introductionmentioning
confidence: 99%